The granite and glacial landscapes of the Peneda-Gerês National Park - Pereira, Paulo (2020)
Granite and glacial landforms are presented as the main geomorphological landscape features of the Peneda-Gerês National Park. The park was established in 1971 and it is the only national park and most important protected area in Portugal. The aesthetic attractiveness is supported mainly by the distinct granite landscape of the Gerês and Peneda Mountains, where the post-orogenic Variscan Gerês gran- ite facies occurs. The rugged relief is poorly covered by vegetation, differentiating it from the surrounding moun- tainous areas and the most distinctive landforms are bornhardts, locally named as “medas”. Typical glacial landforms, such as U-shaped valleys, cirques and moraines, express the sheltered character of a low-altitude glaciation, which is of great significance in the context of the Pleistocene glaciation in Southern Europe.